2018
DOI: 10.15560/14.3.559
|View full text |Cite
|
Sign up to set email alerts
|

First records of Lithobius (Lithobius) forficatus (Linnaeus, 1758) and Lithobius (Lithobius) obscurus Meinert, 1872 (Lithobiomorpha, Lithobiidae) introduced to Colombia

Abstract: The lithobiomorph centipedes Lithobius (Lithobius) forficatus (Linnaeus, 1758) and Lithobius (Lithobius) obscurus Meinert, 1872 are here reported for the first time in Colombia. We examined 193 individuals from collections kept in several universities and natural history museums from Bogotá city were examined. Lithobius forficatus (191 specimens) was recorded up to 2746 m above sea level in areas with some amount of anthropic disturbance. Lithobius obscurus (2 specimens) was recorded at 2700 m above sea level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…According Chagas-Jr et al (2014), in Colombia, this species is only distributed in this region. In this work, the species Scolopendra arthrorhabdoides Ribaut, 1912, is recorded for the department of Bolívar, expanding its distribution which is considered restricted by Chagas-Jr et al ( 2014) and Prado et al (2018); records between 0 and 1300 masl (Prado-Sepúlveda et al, 2016) were found. The list includes the species Trachelodesmus angulatus (Chamberlin, 1923) and T. ancylophor (Chamberlin, 1923) recorded for the Colombian Caribbean by Chamberlin (1923).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…According Chagas-Jr et al (2014), in Colombia, this species is only distributed in this region. In this work, the species Scolopendra arthrorhabdoides Ribaut, 1912, is recorded for the department of Bolívar, expanding its distribution which is considered restricted by Chagas-Jr et al ( 2014) and Prado et al (2018); records between 0 and 1300 masl (Prado-Sepúlveda et al, 2016) were found. The list includes the species Trachelodesmus angulatus (Chamberlin, 1923) and T. ancylophor (Chamberlin, 1923) recorded for the Colombian Caribbean by Chamberlin (1923).…”
Section: Discussionmentioning
confidence: 62%
“…This class comprises five orders: Craterostigmomorpha, Geophilomorpha, Lithobiomorpha, Scolopendromorpha and Scutigeromorpha. The first four are registered for Colombia (Lewis, 1981;Minelli, 2011;Prado-Sepúlveda et al, 2016;Prado et al, 2018). Individuals of Diplopoda class also have a sclerotized body of variable size (between 1.5 and 350 mm in length).…”
Section: Intropica Introducciónmentioning
confidence: 99%
“…Dyachkov, 2019: 14;Bragina et al, 2020: 29;Dyachkov et al, 2022a: 171 DISTRIBUTION. Widespread as anthropochore introductions to North and South America, Greenland, Europe, western Siberia, and Japan [Zalesskaja, 1978;Zuev, Evsyukov, 2016;Prado et al, 2018;Dyachkov et al, 2022a], as well as to Middle Asia: Kazakhstan, the Almaty, Kyzylorda [Dyachkov, 2019], Atyrau and Turkistan regions (present records).…”
Section: Family Lithobiidae Newport 1844mentioning
confidence: 74%
“…Distribution. Lithobius forficatus is distributed in Europe, West Asia, North Africa, the European part of Russia, the Asian part of Russia (known only from the Tyumen Area and Iturup Island, Kuriles), Mongolia, North and South America, Greenland, Australia, and New Zealand (Nefediev et al 2016;Prado et al 2018;Dyachkov 2019). In East Asia, Lithobius forficatus was recorded only from Mongolia and Iturup Island, Kuriles (Zalesskaja 1978;Eason 1996).…”
Section: Lithobius (Lithobius) Forficatus (Linnaeus 1758)mentioning
confidence: 99%